Pectoralis major myocutaneous flap in head and neck reconstruction: an interesting experience from central India regional cancer center - Gupta, Ashutosh; Agrawal, Gunjan; Tiwari, Santanu; Verma, Kshitij; Agrawal, Rajesh; Choudhary, Vivek (International Journal of Research in Medical Sciences, 2017)
Background: Head and neck cancer are sixth most common cancers worldwide with cancer of oral cavity most common. The primary treatment modality for oral cavity cancer has been surgery and defects resulting from the ablation of the tumors require reconstruction. the PMMC flap offer an easy, less time consuming with minimal postoperative complication as a reconstructive option in the hands of reconstructive surgeon. The objective of our study was to give a precise description of our experience with the PMMC flap as a reconstructive option in post-ablative head and cancer surgery. Methods: The current prospective study was conducted in the Department of Surgical Oncology, Regional cancer center, Pt. JNMC, Raipur (C.G.), India from the January 2014 to June 2015. Detailed clinical history and examination of the patients were recorded. All Investigations relevant to the study were done before the surgical procedure. Procedure was performed as per standard protocol and reconstruction was made with PMMC flap. Data was compiled in MS Excel and checked for its completeness and correctness. Then it was analyzed. Results: In the present study male to female ratio was 2:1. Most of the patients belongs to the age group of 41-60 (55.55%) followed by 21-40 (30.15%). In the present study majority of patient of oral malignancy presented with lower alveolus malignancy (36.5%) followed by buccal mucosa malignancy (19.06%). Conclusions: Pectoralis major myocutaneous flap was found to be a versatile flap for reconstruction of large defects in Head and Neck region with minimal complication rate.